2022
DOI: 10.1186/s42358-022-00253-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medications on incidence and risk of knee and hip joint replacement in patients with osteoarthritis: a systematic review and meta-analysis

Abstract: Background This systematic review and meta-analysis aimed to investigate the incidence and risk of knee and hip replacement in patients with osteoarthritis (OA) treated with different medications. Methods OVID MEDLINE, OVID EMBASE, Cochrane and Web of Science electronic databases were searched from inception to May 4th, 2022. Clinical trials, including randomized controlled trials, cohort studies and case–control studies, were selected. The meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
2
4
0
Order By: Relevance
“…Our study showed that 4-to-5 years of NSAID use may not have detrimental effects on structural changes in knees affected with KOA. Our study extends the findings from a recent systematic review and meta-analysis study that associated NSAID use with an increased risk of knee replacements 53 . However, that study 53 included only two case–control studies specifically investigating knee replacement, and it reported high heterogeneity in the meta-analysis results.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our study showed that 4-to-5 years of NSAID use may not have detrimental effects on structural changes in knees affected with KOA. Our study extends the findings from a recent systematic review and meta-analysis study that associated NSAID use with an increased risk of knee replacements 53 . However, that study 53 included only two case–control studies specifically investigating knee replacement, and it reported high heterogeneity in the meta-analysis results.…”
Section: Discussionsupporting
confidence: 86%
“…Our study extends the findings from a recent systematic review and meta-analysis study that associated NSAID use with an increased risk of knee replacements 53 . However, that study 53 included only two case–control studies specifically investigating knee replacement, and it reported high heterogeneity in the meta-analysis results. Therefore, their findings were challenging to interpret.…”
Section: Discussionsupporting
confidence: 86%
“…Clinical information for the patients that received THA was collected by reviewing the electronic patient records, specifically looking at factors that may influence need for THA. This included the nature of their previous operations of the same hip, co-morbidities [ 14 ], medications [ 15 ], smoking status [ 16 ], drug or alcohol abuse [ 17 , 18 ], clinical symptoms prior to THA such as pain and walking ability, and examination findings prior to THA [ 19 , 20 ]. In two cases the exact nature of their previous operations could not be identified.…”
Section: Methodsmentioning
confidence: 99%
“…A 2015 systematic review and meta-analysis of 20 randomized controlled trials (RCTs) described the effect of cognitive behavioral therapy (CBT) versus inactive comparators for treatment of chronic insomnia in adults (N51,162). 1 The review included adults diagnosed with chronic insomnia who did not have medical, psychiatric, or other sleep disorders. Patients received three or more modalities (cognitive therapy, stimulus control, sleep restriction, sleep hygiene, and relaxation) delivered on at least two occasions.…”
Section: Ismentioning
confidence: 99%
“…A 2022 meta-analysis of 40 studies including randomized controlled trials, cohort studies, and case–control studies (N=6,041,254) examined the effect of medications, including corticosteroid injections (CSIs), on risk of total knee arthroplasty (TKA) or total hip arthroplasty (THA) in patients with osteoarthritis (OA). 1 Two of the included retrospective cohort studies evaluated the risk of knee arthroplasty and CSI. One retrospective cohort study compared matched 684 patients with mild-to-moderate knee radiographic OA who did or did not initiate CSI.…”
mentioning
confidence: 99%